Infectious Diseases: Current Epidemiology, Pharmacotherapeutic Strategies, and Global Health Perspectives - Vaibhavi J. Panchal; Hardini P. Chauhan; Hetvi H. Patel; Maitry H. Rathod; Bisojeet R. Khandai (Recent Trends in Infectious Diseases, 2026)
Infectious diseases are still a major health challenge in the world, and there is increased strain on the health systems of nations. This review examines the most important issues in the management of infectious diseases, such as the distribution and effect of infectious diseases across the world, pharmacotherapeutic approaches, and the functions of public health interventions. New threats such as antimicrobial resistance (AMR), the contribution of climate change, and the unequal representation of healthcare are recognized as significant problems. Individualized medicine, vaccine development, and international cooperation are noted to be potential ways to address the problem of infectious diseases in the future. Another type of strengthening of healthcare infrastructure, the enhancement of surveillance systems, and equal access to treatments and vaccines, are also highlighted in the review. The future studies should aim at exploring the interaction between infectious diseases and the environmental factors, new therapeutics, and improving the global coordination to prevent and contain the outbreak of diseases. This holistic strategy is critical to meeting the emerging trend of infectious diseases
Keywords: Climate change; Personalized medicine; antimicrobial resistance; disease surveillance; global collaboration; global health; healthcare disparities; infectious diseases; vaccine development